Spindle Cell Hemangioma in the Mucosa of the Upper Lip: A Case Report and Review of the Literature - Kazuhiro Murakami; Kazuhiko Yamamoto; Tsutomu Sugiura; Tadaaki Kirita (Case Reports in Dentistry)
Spindle cell hemangioma (SCH) is a unique benign vascular lesion. We present a case of SCH in the upper lip of a 41-year-old woman. A submucosal nodular mass 30 × 20 mm in size was observed in the left upper lip. The mass developed 5 years earlier and enlarged after repeated ethanol injections. The mass was elastic firm, mobile, bluish in color, and well demarcated in magnetic resonance imaging. Under the clinical diagnosis of hemangioma, surgical excision was performed under local anesthesia. Microscopically, the lesion was composed of irregular cavernous spaces and multiple solid cellular areas. Cavernous spaces were filled with a mix of erythrocytes and organizing thrombi. The solid areas showed proliferation of spindle-shaped cells arranged haphazardly or in short interlacing fascicles. Immunohistochemically, most cells strongly reacted with vimentin. CD31, CD34, factor VIII, smooth muscle actin, and Wilms tumor-1 reacted with endothelial cells lining the cavernous spaces. The cells within solid areas consisted of mixed cell population with variable reaction for the markers except for factor VIII. From these findings, the diagnosis of SCH was made. Two years after surgery, no recurrence was noted. A review of SCH in the head and neck region is made.